Implementing Port Operation Policy through Collaborative Governance Perspective - Prasetyo, Heri; ., Sumartono; ., Suryadi; Nuh, Mohammad (Journal of Ecohumanism, 2024)
This research aims to explore the operational policy implementation process at the Prigi commercial port by utilizing a collaborative governance framework. This study uses policy implementation theory (Van Meter & Van Horn, 1975) which focuses on dimensions such as standards and resources, communication objectives, interorganizational characteristics, and enforcement activities of implementing agencies, economic, social, and political conditions, implementer dispositions, and performance. Additionally, it integrates collaborative governance theory (Emerson & Nabatchi, 2015) which emphasizes the importance of cooperation, coordination, and involvement of various stakeholders, including government port operators, port users, and local communities, in designing and implementing such policies. This approach is believed to improve the effectiveness, efficiency and sustainability of port operations, ensuring that policies reflect diverse interests and needs. This research adopted a qualitative descriptive approach and was conducted at the Prigi commercial port, Trenggalek Regency, Indonesia. Thirty-two informants participated in this research, consisting of government officials including legislators (DPRD) and executives (regents, regional government secretaries, regional planning agencies, transportation agencies, and development administration bureaus), private sector representatives (business associations), NGOs, academics, community leaders, and the media. Findings show that operational policy implementation at Prigi port faces challenges due to lack of clarity in policy standards and objectives, limited human resources, weak inter-organizational communication, complex characteristics of implementing agencies, and limited commitment from regional leaders as well as low involvement of NGOs, academics, leaders society, and media. This study recommends the issuance of a Memorandum of Understanding (MoU) as an agreement of honor between all stakeholders to optimize the operations of the Prigi commercial port. In addition, this research provides opportunities for further research using alternative perspectives of policy implementation theory and collaborative governance theory in port governance.